Pregnancy rates in beef cattle after administration of GnRH agonist 11 to 14 days after insemination - Rettmer, I.; Corah, L.R.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pregnancy rates were assessed in suckled beef cows (n=145) and virgin beef heifers (n=606) of mixed breeding following an injection of either 100 or 200 μg of a GnRH agonist given once on d 11-14 after estrus and insemination. In heifers, the 100 μg dose improved (P<.08) pregnancy rates, based on rectal palpation of the uterus, and at both doses, based on actual calving dates. There was no effect of either dose on pregnancy rates of suckled cows, based on palpation results, but actual calving showed a 21% increase (P<.08) in pregnancy rates in cows treated with 100 μg of the GnRH agonist.
Keywords: Beef; GnRH Agonist; Pregnancy rates; Suckled cows; Heifers